Differential Contribution of Anterior and Posterior Midcingulate Subregions to Distal and Proximal Threat Reactivity in Marmosets. (1st June 2021) - Rahman, Sufia S; Mulvihill, Kevin; Wood, Christian M; Quah, Shaun K L; Horst, Nicole K; Clarke, Hannah F; Cockcroft, Gemma J; Santangelo, Andrea M; Roberts, Angela C
Abstract: The midcingulate cortex (MCC) is associated with cognition and emotion regulation. Structural and correlational functional evidence suggests that rather than being homogenous, the MCC may have dissociable functions that can be mapped onto distinct subregions. In this study, we use the marmoset monkey to causally investigate the contributions of two proposed subregions of the MCC: the anterior and posterior midcingulate cortices (aMCC and pMCC) to behavioral and cardiovascular correlates of threat processing relevant to anxiety disorders. Transient inactivation of the aMCC decreased anxiety-like responses to a postencounter distal threat, namely an unfamiliar human intruder, while inactivation of the pMCC showed a mild but opposing effect. Furthermore, although inactivation of neither MCC subregions had any effect on basal cardiovascular activity, aMCC inactivation blunted the expression of both cardiovascular and behavioral conditioned responses to a predictable proximal threat (a rubber snake) during the extinction in a Pavlovian conditioning task, with pMCC inactivation having again an opposing effect, but primarily on the behavioral response. These findings suggest that the MCC is indeed functionally heterogeneous with regards to its role in threat processing, with aMCC providing a marked facilitative contribution to the expression of the emotional response to both proximal and distal threat.